Analisis Kepuasan Pelanggan pada Alfa Mart Kalisari Jakarta - Iskamto, Dedi (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This study aims to find out how much customer satisfaction at Alfa Mart Kalisari Pasar Rebo Jakarta to the quality of service that has been given. Where organiasasi required to be able to meet customer satisfaction and adjust customer desires so the company should be able menditeksi what the market needs or consumer desires and read and translate any changes in the situation as an opportunity. The company will not grow without customers. The more customers, the company will be able to compete with other companies in this era of globalization. The company should be able to satisfy and retain existing customers Research location in Alfa mart Husnayain Kalisari Pasar Rebo East Jakarta with The analysis of data is descriptive Quantitative, Data analysis tools used are: Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and Gap Analysis (GAP). With a total of 120 respondents and a confidence level of 95 percent